The equation 6 + y = 12 is a simple equation in one variable. If you add 6 to both sides of the equals sign, you get y = 18, and that is the solution.
No. 3a 12 plus a 6 is not a solution Of an equation.
The solution to this equation is that h is equal to -4. You can substitute this value for h into the equation to get -4 x -9 - 6 plus 12 x -4 plus 40 equals 22, or 36 - 6 plus - 48 plus 40 equals 22.
No. The equation describes a straight line and the coordinates of any one of the infinitely many points on the line is a solution.
-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.
It's an equation and its solution is: x = -12
The equation is y + 2 = 12.
The equation seems to equal 72.
The equation -7 plus 12 equals out to be five. This is a math problem.
If (-12, 24) satisfies the equation (makes it a true statement), then it is a solution to the equation. Chek: y = x + 12; replace y with 24, and x with -12 24 =? -12 + 12 24 = 0 false Therefore, (-12, 24) is not a solution.
x = 12 and y = 8
No equation equals 12, but there are an infinite number of equations for which 12 is a solution. Here are a few: x + 1 = 13 2x - 6 = 18 x2 = 144 x = log(1,000,000,000,000)
There is no equation. An equation is true, whereas the statement ( 5 + 7 = -12 ) is false.
Yes, because the equation is linear, there is only one solution:4x - 3 = 12 +2x4x - 2x = 12 + 32x = 15x = 7.5There is no other solution
what is the slope of the line that has the equation 4x+2y=12?
Both of them are equations!The solution is (x, y) = (2, 1).
It is: y = -4x+12
Is an equation of a straight line in 3 dimensions. It cannot be simplified further, and a solution for any of the variables requires another two [independent] equations.
y = 10
2x+3y=12 ......1st equation 3x+2y=13 .......2nd equation ____________________________________ multiplying 1stt equation by 3 and 2nd equation by 2 3x(2x+3y=12) 2x(3x+2y=13) _______________________________ now the equations become 6x+9y=36 ...3rd 6x+4y=26 ....4th by solving both equation(substractinf 4th from 3rd) we get.. 5y=10 therefore y=2 and x=3